PENGARUH LATIHAN TARGET TERHADAP KETEPATAN SHOOTING KAKI BAGIAN DALAM PEMAIN FUTSAL JAVA EAGLE TUGUMULYO - Wawan Syafutra; M. Eric Kantona; Depiyanti Depiyanti (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to determine whether there is an effect of Target training on the accuracy of shooting the inner legs of Java Futsal player Eagle Tugumulyo. This research method is an experiment with the One Group pretest-posttest Design design, which is an experiment carried out on one group only without comparison. The population in this study was all Java Eagle Tugumulyo Futsal players totaling 20 people with a sample of 10 people. Samples were randomly selected from Java Futsal player Eagle Tugumulyo. The instrument used tests the ability to shoot to targets on the futsal playing field that has been marked and numbered. Based on the paired sample test results, it shows a significant value between the pretest and posttest values with significance values (2-tailed) p = 0.00 < 0.05 calculated values (6.220) > ttable (1.833). This result also shows Ha: accepted and Ho: rejected